The Effect of Management Control in Purchase Volume on The Level of Food Ingredients Damage at Elcavana Hotel Bandung - Asyari Cahyaningtyas; Ignatius Oki Dewa Brata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
In this study, researchers wanted to test the theory whether there is an influence of management control in controlling the purchase volume of the level of damage to food. The population of this research is the management of Elcavana Hotel Bandung in the accounting department and the kitchen department. Procurement of the ingredients for a certain period can not be predicted accurately. In other words, the ingredients ordered by the relevant department are not in accordance with the realization of the use of each day because there are some menus that do not sell well (slowmoving). The controlling of prices and quality of ingredients is carried out with the main objective to avoid the swelling of production costs due to food ingredients that are not in accordance with standards and to set the selling price of food. After being tested using simple linear regression, the results are as previously thought. The controlling of the volume of food purchases greatly affects the level of damage to food ingredients at Elcavana Hotel Bandung. So, the stronger the management control in the purchase volume, the lower the level of food damage.